An Elliptical-Core Few-Mode Fiber with Low Loss and Low Crosstalk for the MIMO-FREE Applications - Gao, Yan; Li, Yanlei; Li, Xin; Zheng, Hongjun; Bai, Chenglin; Hu, Weisheng; Xu, Hengying; Dong, Qiuhuan; Xing, Huadong; Su, Yingqun; Yin, Yingxin; Wei, Chongqi; et al. (Frontiers in Physics, 2022)
In this invited paper, a novel elliptical-core few-mode fiber (EFMF) with low loss and low crosstalk is proposed for multiple input multiple output free (MIMO-FREE) applications. The EFMF, which adopts pure silica elliptical core with step refractive index profile and trench refractive index, can be used in MIMO-FREE operation. The result using a full vector finite element method shows that the proposed EFMF breaks the mode degeneracy and achieves mode maintaining function. The EFMF performs five non-degenerate modes operation with the modes LP01, LP11a, LP11b, LP21b and LP21a for the MIMO-FREE applications. The mode crosstalk of the EFMF is effectively reduced using the large effective refractive index difference between the modes. If the data rate or capacity is conventionally set a multiple of 2, the transmission system can be upgraded using the EFMF with four modes operation where the effective refractive index difference between any two modes is more than 2×10-3. Pure silica core is employed to effectively reduce intrinsic loss. The low bending loss is realized by using the trench refractive index at the cladding. The EFMF can be applied to the good transmission of mode division multiplexing in MIMO-FREE applications while eliminating the difficulty and complexity of the MIMO digital signal processing.